2022
DOI: 10.1002/app.52827
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal stability and impact strength of phenolic formaldehyde resin using acid‐treated basalt scales

Abstract: In this study, phenolic formaldehyde (PF) resin-based composites were prepared using basalt scale (BS) as a reinforcing agent via a melting-blending method. The BS surface was treated with hydrochloric acid, and the surface properties were characterized using thermal field-emission scanning electron microscopy, Fourier-transform infrared, X-ray photoelectron spectrometry, and energy-dispersive X-ray spectroscopy. Moreover, the influence of acidtreated BS (H-BS) content on the thermal properties, flexural prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Liu et al (2016) prepared BF-reinforced friction materials and found that when the content of BF was 12%, the wear was minimal and the noise performance was optimal. Li et al (2022) found that the thermal stability of phenolic resin reinforced by acid treated basalt flakes was significantly improved, The impact strength also reached 153% of the original phenolic resin. Kun et al (2023) found that the use of BF can improve friction stability while also improving the heat resistance of friction materials and limiting the friction fluctuation range to 0.040-0.110.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Liu et al (2016) prepared BF-reinforced friction materials and found that when the content of BF was 12%, the wear was minimal and the noise performance was optimal. Li et al (2022) found that the thermal stability of phenolic resin reinforced by acid treated basalt flakes was significantly improved, The impact strength also reached 153% of the original phenolic resin. Kun et al (2023) found that the use of BF can improve friction stability while also improving the heat resistance of friction materials and limiting the friction fluctuation range to 0.040-0.110.…”
Section: Introductionmentioning
confidence: 93%
“…The composition of BF-reinforced resin-based friction material formula is shown in Table 1, with S01–04 as the experimental group. According to relevant research, (He et al , 2020; Kun et al , 2023; Li et al , 2022; Zhao et al , 2020), the content of BF gradually increases from 10% to 16%. S0 is the comparative group; BF is not added.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…[ 15 ] Notably, basalt scales (BS), one of the most abundant silicate minerals, demonstrate excellent thermal and chemical stability, as well as sound absorption, especially in mechanical and electrical insulating properties, due to their distinctive chemical composition and structure. [ 16 , 17 , 18 , 19 , 20 ] Nevertheless, BS have not been utilized in the electrical insulating field despite their outstanding physical and chemical properties. Assembling BS with ANF to fabricate the composite micropapers may be a promising way to fully realize their inherent potential.…”
Section: Introductionmentioning
confidence: 99%
“…In the research field of heavy anti-corrosion coatings, inorganic scaletype filler has a wide range of applications, and is more comprehensive and effective to meet the performance requirements of anti-corrosion coatings modifiers [20,22,23]. Compared to the traditional glass flake and other fillers, basalt flake filler type anti-corrosion coatings not only have a stronger filling effect and physical shielding effect, but their environmental economics can further reduce the cost of coatings [24,25]. Yan et al [26] added basalt flakes to a solvent-free epoxy resin and showed that the coating with 10% basalt flakes added had the best corrosion protection.…”
Section: Introductionmentioning
confidence: 99%